Factors Influencing Sharia Digital Banking Utilization by Millennial Generation in Indonesia - Sarifah, Siti (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze factors influencing sharia digital banking utilization by using modified Technology Acceptance Model (TAM) approach. The data in this study were collected through questionnaires distributed online. The sample used in this study was 125 millennial respondents who used Jago Syariah Bank and Aladin Syariah Bank. In this study, the data is analyzed by using structural equation model analysis with the SmartPLS 3.2.9 analysis tool. The results showed that perceived ease of use, self-efficacy, and consumer innovativeness positively and significantly affect sharia digital banking utilization. However, there are some variables that have no significant effect, which are, perceived usefulness and subjective norms.